The Institutional Work of IFRS Adoption in Telco Company: Transformation from US GAAP to IFRS - Winda Susliani; Ersa Tri Wahyuni; Evita Puspitasari (Jurnal Akuntansi Bisnis, 2022)
AbstractThe literature on the IFRS adoption process to date has mainly focused on the macro level. This paper draws on an in-depth longitudinal analysis of the Indonesian company PT Telekomunikasi Indonesia Tbk to understand the role of institutional work in the transformation of organization from US GAAP to IFRS. The paper examines the work of actors to disrupt, create, and maintain the institution during the transition to IFRS. The study has revealed that the IFRS adoption at the company is beyond a shallow compliance of financial reporting standards but has significant impact on the company’s transformation as a whole. The IFRS adoption has transformed the business process and the organization culture. The study has also revealed that there are different types of institutional works during the four stages of institutional transformation of the company: Stability, Conflict, Change and Implementation. The tone of the top management board in the organization is crucial to the key actors to stay committed to the long transformation process. This paper contributes to the literature of the IFRS adoption process by providing a framework of the IFRS adoption at the micro level. The case study may assist other companies in their real transformation through embracing the IFRS.   AbstrakLiteratur tentang proses adopsi IFRS sampai saat ini terutama berfokus pada tingkat makro. Makalah ini mengacu pada analisis longitudinal mendalam dari perusahaan Indonesia PT Telekomunikasi Indonesia Tbk untuk memahami peran kerja institusional dalam transformasi organisasi dari US GAAP ke IFRS. Makalah ini mengkaji pekerjaan para aktor untuk mengganggu, menciptakan, dan memelihara institusi selama transisi ke IFRS. Studi tersebut telah mengungkapkan bahwa adopsi IFRS di perusahaan berada di luar kepatuhan standar pelaporan keuangan yang dangkal tetapi memiliki dampak signifikan pada transformasi perusahaan secara keseluruhan. Adopsi IFRS telah mengubah proses bisnis dan budaya organisasi. Studi ini juga mengungkapkan bahwa ada berbagai jenis pekerjaan institusional selama empat tahap transformasi institusional perusahaan: Stabilitas, Konflik, Perubahan dan Implementasi. Nada dewan manajemen puncak dalam organisasi sangat penting bagi para aktor kunci untuk tetap berkomitmen pada proses transformasi yang panjang. Makalah ini berkontribusi pada literatur proses adopsi IFRS dengan menyediakan kerangka kerja adopsi IFRS di tingkat mikro. Studi kasus dapat membantu perusahaan lain dalam transformasi nyata mereka dengan merangkul IFRS.